Manajemen Perguruan Tinggi di Indonesia: Usaha Memenangkan Persaingan Industri Jasa Pendidikan - Wulani, Fenika (Jurnal Widya Manajemen & Akuntansi, 2003)
In the globalization era and taster changing environment, universities in Indonesia must be adapted in order to survive in the future. Quality can be improved by effective management function, chance to develop human resources' creativity, costumer oriented, and trying to fit course programs with business world. University also must be concerned with employee' s need, because the characteristic of service company, the people that provided service is important. If universities want to do that, sustainable growth can be reached.